2016
DOI: 10.1016/j.ejim.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of drugs on the kidney

Abstract: The number of drugs presently marketed is countless, their prescription is relentlessly growing, such that the likelihood of adverse effects is strikingly increasing. As many drugs are cleared by the body through kidney excretion, renal adverse events are likely. In this review we shall concisely describe the pathophysiologic mechanisms of renal damage by drugs, the different clinical presentations outlining renal toxicity in the course of pharmacologic treatment, and the main offending agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 89 publications
(104 reference statements)
1
21
0
Order By: Relevance
“…Mild congestion and shrinkage of glomerulus observed in the group treated dihydroartemisinin/piperaquine may indicate renal toxicity. Drugs can exert toxic effect on the glomerulus [31]. As most drugs are excreted by the kidney, it is reasonable to assume that the kidney itself could be a privileged target of their toxic action [31].…”
Section: Discussionmentioning
confidence: 99%
“…Mild congestion and shrinkage of glomerulus observed in the group treated dihydroartemisinin/piperaquine may indicate renal toxicity. Drugs can exert toxic effect on the glomerulus [31]. As most drugs are excreted by the kidney, it is reasonable to assume that the kidney itself could be a privileged target of their toxic action [31].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, there is some evidence indicating pharmacokinetic or pharmacodynamic differences and variability among different various SGLT2 inhibitors. The likelihood of renal‐related adverse events may depend on whether and to what extent the drug is cleared from the body through kidney excretion . It is reported that ~75% of dapagliflozin is eliminated by the renal pathway, while the other 2 SGLT2 inhibitors appear to be less subject to renal clearance (33% of canagliflozin and 54% of empagliflozin) .…”
Section: Discussionmentioning
confidence: 99%
“…The likelihood of renal-related adverse events may depend on whether and to what extent the drug is cleared from the body through kidney excretion. 42 It is reported that~75% of dapagliflozin is eliminated by the renal pathway, while the other 2 SGLT2 inhibitors appear to be less subject to renal clearance (33% of canagliflozin and 54% of empagliflozin). [43][44][45] , will not only provide enough statistical power to determine the renal safety of SGLT2 inhibitors, but also solve the issue of whether or not the renal benefit is a class effect or a specific drug effect.…”
Section: Discussionmentioning
confidence: 99%
“…The protease inhibitor, indinavir, and to a lesser extent atazanavir, is poorly soluble in urine and can potentially cause crystalluria with subsequent interstitial nephritis and, rarely, parenchymal fibrosis ( 150 ). Although some medications, specifically those employed as immunosuppressants, have been associated with diffuse fibrosis and sclerosis secondary to increased expression of TGF-β ( 151 ), direct links between indinavir-mediated fibrosis and TGF-β1 have not been evaluated.…”
Section: Renal Disease and Its Relationship To Haart-mediated Toxicitmentioning
confidence: 99%